The Parallel Development of the Feminine Ending -at in Semitic Languages - Blau, Yehoshuaʿ 1919-2020 (1980)
Many Semitic languages exhibit the tendency to drop the t of the feminine ending -at in the absolute, leading to an exceptional morphological alternation a in the absolute: -at in the construct. Although, as a rule, exceptional morphological facts most strongly attest to inherited features, the exceptional morphological alternation a : at in various Semitic languages has to be interpreted as due to parallel development, because it arose at different times in different languages and because of many differences in details. It was because of the basic similarity of the Semitic languages that they developed in the same direction even in small details, making it the more arduous to differentiate between common heritage and parallel development. The bulk of the paper is devoted to the analysis of the constraints of the loss of t in -at in the various Semitic languages, stressing the differences between them in detail.
Keywords: Semitistik; Hebräisch